From Peru to Bolivia. Between anarchism, radical liberalism, and literary vanguardism, 1902-1918 - Margarucci, Ivanna (2023)
In the Andean region, the processes of ideological dissemination and reception of the left-wing currents have been studied on the basis of a model constructed according to the Atlantic area of the continent. Rather than European immigration, in the Bolivian case, the regional dissemination routes were responsible for the arrival of socialism and anarchism. Thus, in this article, we propose to reconstruct the route traced in the heart of that region thanks to the intervention of some artisans, professionals and men of letters such as the Peruvians Carlos del Barzo, Mariano Lino Urquieta, and Arturo Pablo Peralta Miranda and the Bolivian Gustavo Adolfo Navarro, who moved intellectually and physically from Peru to Bolivia and vice versa between 1902 and 1918. Based on an extensive documentary corpus built in Bolivian and Peruvian repositories composed of commercial and radical press, cultural magazines and literature, this essay on the social history of ideas hypothesizes that the diffusion that these characters made of anarchism confused with radical liberalism and literary vanguardism, together with the ideas of the famous Manuel González Prada which influenced them, contributed to the process of radicalization and ideological emancipation of the Bolivian labor movement and left-wing currents.